JURIDICAL STUDY ON CRIMINAL IN THE CRIME OF HUMAN TRAFFICKING ACCORDING TO LAW NO. 21 OF 2007 (CASE STUDY OF DECISION NO. 3119/PID.SUS/2020/PN. MDN) - Immanuel Simanjuntak; Dimarciano Abelardi Sagala; Melinda Putri Ayu Tumangger; Arina Uly Febiola Sihite (Awang Long Law Review, 2022)
Human trafficking is a modern form of slavery. The victims are trafficked not only for prostitution but also include other forms of exploitation where in this case Human rights are violated, such as forced labor or forced services, slavery, or practices similar to the slavery are also traded. This case has become a symptom all over the world especially in Indonesia, the development of the era and social medial at this time is dangerous and makes people more and more willing to do whatever without worrying about their own safety. The problem in this research is the application of law against the perpetrators of the criminal act of Human trafficking reviewed in law number 21 of 2007 concerning the eradication of the crime of Human trafficking, the factors causing the crime of Human trafficking, as well as the judge's considerations in sentencing the perpetrators of the crime of Human trafficking in the decision No.3119/ Pid.Sus /2020/ PN.Mdn This study is using a normative juridical research method which is a community social research followed by a literature study by examining the secondary data obtained by conducting a literature study. The consideration of the judges of the Medan State Court in deciding the case No.3119/ Pid.Sus /2020/ PN.Mdn has considered this case well based on the proven evidence and facts in the trial. The aggravating and mitigating circumstances halve been considered by the panel of judges, so that the judge's decision has fulfilled a sense of justice for the community.